Sacubitril-Valsartan in LVAD Patients: Potentials for the Future? - Arshad, Samiullah; Haq, Tayyaba; Stephens, Dan; Vaidya, Gaurang N (Cardiology and Cardiovascular Medicine, 2022)
Beneficial effects of Angiotensin Receptor Neprilysin Inhibitors (ARNIs) in heart failure patients are increasingly being recognized. Current literature on ARNIs among LVAD patients is based on small retrospective studies; however, these reports suggest their acceptable tolerability, effective blood pressure control and improvement in NTproBNP levels. As we continue to better understand their cardio-protective effects including potential of myocardial recovery their use in patients with LVADs is bound to increase. Side effects that may limit their tolerability include acute kidney injury, hypotension, hyperkalemia and angioedema. Clinical trials are ongoing to assess their safety and tolerability in LVAD patients.